The personal library and indexing management information system (PLIMIS) / Choong Wai Kit - Choong, Wai Kit (2001)
The Personal Library and Indexing Management Information System (PLIMIS) is an information system used to organize and manage personal collections of reading materials such as books, journals, journal articles, magazines, articles, dictionaries and CD-ROMs. The system allows easy searching and retrieving of the items in the collections as it adopts a systematic classification and indexing for the reading materials. This will save the time in searching a specific item. PLIMIS is designed for personal use and contains most of the features in the current library information systems. It provides user friendly interface and help to the users for easy using and understanding. The systems are divided into two models, administrator mode and user mode. The administrator is allowed to add delete the information of reading materials and also add or delete users in the database. The Users authorized people who can search and retrieve data from the system after a successful login. Title indexing is used for searching and retrieving of records. The Dewey decimal classification with author indexing are used for arranging and placing of reading materials on the shelves for easy finding. The searching methods which can be used are by title, subject and author. All the related reading materials will be displayed for the user in a sorted form. The methodology of developing PLIMIS is based on the software prototyping, model. This system will be developed using Microsoft Visual Basic 6.0, Microsoft Access 97 as it database and Seagate Crystal Report 7 to generate report.